One valley and a thoousand - "Kligensmith, Danial" (New Delhi, 2007)
By the end of the twentieth century, more then 45,000 large dams were built world wide displacing millions of people, and dramatically altering both ecosystems and social systems centered on rivers. A majority of these dams were constructed after 1945. This book seeks to explain the enormous global investment in dams since 1945 and explores their connections to political ideologies. It shows the lack of concern and awareness of policymakers and electorates about the human tragedies. It also sheds light on the disappointing performace of many river valley projects. The author traces the history of the politics and the political culture that influenced economic and technical decisions in the creation of particular dams in India and the United States. In doing so, he contributes to a broader discussion on the politcal significance of dams worldwide, and of the connections between development and nationalism.
Keywords: Dams